Development of amine modified K2CO3/Al2O3 solid sorbent with exhaustion indicator for direct air capture of CO2. (December 2022) - Nokpho, Pacharapol; Piemjaiswang, Ratchanon; Sema, Teerawat; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon
Abstract: Air quality has a significant impact on the health of the people especially inside buildings that use closed air conditioning systems. When the indoor air quality level is below the standard but the people are unable to detect and continue to work in that area, it may affect to human health and cause respiratory disease. In this study, a carbon dioxide (CO2 ) sorbent based on the synthesis of potassium carbonate/gamma-alumina ( K 2 CO 3 / γ -Al2 O3 ) modified with amine-based solvents was developed. The sorbent exhaustion was indicated by observing the indicator color change for indoor direct air capture of CO2 . The results showed that the modified sorbent had adsorption capacity around 60–64 mg CO2 /g sorbent under room temperature and atmospheric pressure. The modified sorbent could successfully demonstrate its exhaustion by changing color of the sorbent. In addition, the exhaustion sorbents could also be reused by thermal regeneration process using conventional microwave oven due to the low power consumption and less regeneration time.